(untitled) (European Journal of Education and Psychology, 2018)
The aim of the present study is to assess the risks associated with parental breakup on the children’s physical health indicators in relation to adaptive and maladaptive behaviour. A cross-sectional designed study was conducted to assess the physical health indicators of children in relation to the family type (intact homes vs. separated parents). The study was performed in the Primary Healthcare Area of the University Hospital of Santiago de Compostela (Spain). The sample consisted of 467 children and adolescents, of whom 300 (64.2%) were from broken homes, and 167 (35.8%) from intact families. The data on physical health were gathered using a structured interview, the Structured Developmental History of the BASC. Children living with separated parents had approximately double the risk of gastrointestinal, genitourinary, dermatological and neurological disorders than children in intact families. Parental breakup is a risk factor for the children’s physical health in terms of genitourinary, gastrointestinal, dermatological, and neurological disorders.